Legal analysis of the ratio legis behind risk-based business licensing reform in Indonesia: a study of PP No. 24/2018 and PP No. 5/2021 - S. N. Rachmania; Sukarmi; S. Hadiyantina (Law and Safety)
The transition from Government Regulation No. 24 of 2018 to Government Regulation No. 5 of 2021 in Indonesia marks a strategic regulatory reform, shifting towards a risk-based business licensing system through the Online Single Submission platform. This transformation reflects Indonesia’s efforts to streamline its regulatory environment, improve Ease of Doing Business rankings, mitigate regulatory overlaps, and align with international best practices. Given the critical role of an efficient business licensing system in fostering economic growth and attracting foreign investment, understanding the legislative rationale (ratio legis) behind this transition is essential. This study employs a normative juridical approach, incorporating statutory and conceptual analysis, along with content analysis of relevant legal materials to systematically assess the impact of these regulatory changes. The research focuses on the efficiency of the reformed licensing process, its role in corruption reduction, and its influence on Indonesia’s Ease of Doing Business performance. Findings indicate that Government Regulation No. 5 of 2021 addresses previous inefficiencies and inconsistencies by introducing a more integrated, standardized, and transparent licensing framework. The implementation of a risk-based model streamlines business licensing procedures, ensures greater legal certainty, and reduces excessive bureaucratic intervention, thereby creating a more business-friendly and investment-attractive environment. The study highlights how Online Single Submission facilitates a more accessible, structured, and digitized licensing system, allowing both domestic and foreign investors to operate within a regulatory framework that ensures transparency, accountability, and predictability. By effectively implementing these reforms, Indonesia enhances its legal certainty and economic competitiveness, thereby positioning itself as a stronger player in the global investment landscape. These regulatory improvements are expected to contribute to a more equitable and prosperous business ecosystem, ultimately supporting sustainable economic growth and enhanced investor confidence.